Peer Attachment and Cyberbullying in Junior High School Students Reviewed from Gender and Class Level - Mustasyar, Rabiatul Adawiah Al; Jalal, Novita Maulidya; Rasyid, Nurfajrianti (Universitas Pahlawan Tuanku Tambusai, 2026)
Cyberbullying has increasingly emerged as a serious issue along with the intensive use of social media among students. This study aimed to examine differences in peer attachment and cyberbullying behavior among junior high school students based on gender and grade level. A quantitative approach was employed, involving 245 students of SMP Negeri 11 Makassar selected through accidental sampling. Data were collected using peer attachment and cyberbullying scales and were analyzed using nonparametric tests, namely Mann–Whitney and Kruskal–Wallis tests. The results show a significant difference in cyberbullying behavior based on gender, with female students displaying higher levels than male students, while peer attachment does not significantly differ by gender. Based on grade level, cyberbullying behavior significantly differs, with eighth-grade students showing the highest tendency, whereas peer attachment is strongest among seventh-grade students. These findings indicate that positive peer relationships play an important role in reducing cyberbullying behavior during adolescence.